Exploring the harmony between contemporary values and Islamic identity through the lens of the Gülen movement's teachings - Gurkan, Emre Arda; Provedel, Davide; Ercan, Richard (Journal of Religion and Linguistics, 2024)
There is a growing need for new Muslim identities that reflect global realities. Fethullah Gülen, a notable Turkish-Muslim cleric, is influential and persuasive. Gülen emphasizes spirituality, religious pluralism, discussion, and education to promote peaceful coexistence and integrate faith and reason in Western democracies. This study examines how Gülen's ideas and the global volunteer organization he created promote Muslim-non-Muslim harmony. We use text linguistics' seven principles—cohesion, coherence, intentionality, acceptability, informativity, situation, and intertextuality—to assess Gülen's teachings and movement. In the social sciences, we also use textual language norms as a fresh theoretical and methodological approach to studying social movements and events. This study's focus on movement-text relationships and cognitive processes in information creation, reproduction, and dissemination makes it distinctive. This study investigates these issues in Muslim countries, multicultural cultures, and liberal democracies. This research is useful because it explains the Gülen movement's domestic and worldwide advancements. This article figuratively depicts Fethullah Gülen as the author, his movement as the text, and humanity as the readers.